Dietary patterns and their socioeconomic factors of adherence among adults in urban Burkina Faso: a cross-sectional study - Weil, Konstantin; Coulibaly, Issa; Fülbert, Hannah; Herrmann, Alina; Millogo, Roch Modeste; Danquah, Ina (Journal of health, population and nutrition, 2023)
Sub-Saharan African populations undergo a nutrition transition towards diets associated with increased risk for metabolic and cardiovascular diseases. For targeted prevention, we aimed to characterize dietary patterns and determine their sociodemographic factors of adherence.
Gesehen am 09.08.2024